"Cow Is a Mother, Mothers Can Do Anything for Their Children!" Gaushalas as Landscapes of Anthropatriarchy and Hindu Patriarchy. (2019) - Narayanan, Yamini
Abstract : This article argues that gaushalas, or cow shelters, in India are mobilized as sites of Hindutva or Hindu ultranationalism, where it is a "vulnerable" Hindu Indian nation—or the "Hindu mother cow" as Mother India—who needs "sanctuary" from predatory Muslim males. Gaushalas are rendered spaces of (re)production of cows as political, religious, and economic capital, and sustained by the combined and compatible narratives of "anthropatriarchy" and Hindu patriarchy. Anthropatriarchy is framed as the human enactment of gendered oppressions upon animal bodies, and is crucial to sustaining all animal agriculture. Hindu patriarchy refers to the instrumentalization of female and feminized bodies (women, cows, "Mother India") as "mothers" and cultural guardians of a "pure" Hindu civilization. Both patriarchies commodify bovine motherhood and breastmilk. which this article frames as a feminist issue. Through empirical research, this article demonstrates that gaushalas generally function as spaces of exploitation, incarceration, and gendered violence for the animals. The article broadens posthumanist feminist theory to illustrate how bovine bodies, akin to women's bodies, are mobilized as productive, reproductive, and symbolic capital to advance Hindu extremism and ultranationalism. It subjectifies animal bodies as landscapes of nation‐making using ecofeminism and its subfield of vegan feminism.